The Adoption of Virtual Fitting Rooms in Iranian Sportswear Industries: A Mixed-Methods Study Based on TAM Model - Seyyed Iman Ghaffarisadr; Farzad Nobakht Sareban (Sports Business Journal)
Purpose: Virtual fitting rooms allow online sportswear consumers to try on clothes before shopping. This technology has recently received much attention due to its many benefits to sports consumers and commercial potential. Still, it has not yet entered Iran, and there is no information regarding its adoption by Iranian consumers. This research investigates the adoption of this technology by Iranian online sportswear consumers.Methodology: This research is applied and developmental in terms of purpose and exploratory in terms of implementation method. In this research, a mixed method (quantitative, qualitative) has been used, in which the Delphi qualitative method precedes the quantitative method. In the qualitative phase, 20 experts in the sportswear industry were selected through snowball sampling. In the quantitative phase, a survey of 394 online shoppers of sportswear products was conducted on social networks. Structural equation modelling was used to test the hypotheses. SMART PLS and SPSS 23 software were used for data analysis.Findings: The results supported the positive effect of the factors perceived ease of use, perceived usefulness, perceived enjoyment, and fashion leadership, as well as the negative impact of technology anxiety on adopting this technology. The results have practical implications for sports managers, retailers, and sportswear industries regarding adopting the best management and marketing strategies for virtual fitting rooms.Originality: This study examines the innovation of virtual fitting room technology among Iranian sportswear consumers for the first time. Virtual fitting rooms play a significant role in saving time, energy, and money for sports consumers and protecting their privacy. Also, this technology is a fantastic promotional device for sports industries and retailers if Iranian sportswear consumers accept it.